Demethylbellidifolin, a potential aldose reductase inhibitor ameliorates diabetic nephropathy by regulating the polyol pathway - Haifei Xie; Qilin Tong; Zhinan Xiang; Chenggao Zhou; Luo-Sheng Wan; Jiachun Chen (Elsevier, 2022)
Background: Lots of plants in genus Swertia are widely used in the traditional medicine as the treatment for T2DM and its complications in Asia. However, the pharmacodynamic material basis and underlying mechanisms of these plants are still incompletely studied. Inhibition of aldose reductase to regulate polyol pathway is considered to be one effective strategy to treat many complications arising from diabetes. Aim: The inhibitory effect against aldose reductase of typical components from the genus Swertia were examined, and further verified in db/db mice model to explore its in vivo renal protective ability and underlying mechanism. Methods: Human recombinant aldose reductase (AR) was applied to detect the inhibitory activity of these components from genus Swetia in vitro, and the most active one was further analyzed in molecular docking experiment. Then, db/db diabetic mice model were employed to investigate the renal protective effects in vivo. Oxidative stress and renal function related indicators were determined using biochemical kit. Histopathological examination of kidney was conducted to evaluate pathological variations. RT-PCR was applied to measure the level of AR mRNA in renal cortex. Expression of AR, TGF-β1, Collagen Ⅳ, Nephrin and Podocin in kidney tissues were assessed by Western blot. Results: It turned out that demethylbellidifolin (DMB) showed the strongest inhibitory activity against AR, with an IC50 of 1.29 ± 0.16 μM, by stabilizing the active site of AR. In vivo experiment confirmed that DMB could remarkably reduce blood glucose and albuminuria level, and alleviate oxidative stress response. Meanwhile, histopathological examination also displayed that the kidney damage in db/db mice was significantly improved after treatment with DMB. Further mechanism study indicated that DMB could prevent the accumulation of sorbitol, one of the polyol pathway products. Besides, DMB could also maintaining the integrity of podocytes structure by up-regulating the expression of Nephrin and Podocin, and exert renal protective effects by inhibiting the expression of AR, Collagen Ⅳ and TGF-β1 in the polyol pathway. Conclusions: These findings indicated that genus Swertia could be an important plant sources of aldose reductase inhibitors, and one of its typical components, DMB, exerted a therapeutic role in the treatment of diabetic nephropathy by regulating the polyol pathway to relieve the injury of cells in the kidney, and may represent a promising renal protective medication for diabetic nephropathy therapy.